Epidural Auditory Event-Related Potentials in the Rat to Frequency and duration Deviants: Evidence of Mismatch Negativity? - Nakamura, Tamo; Michie, Patricia T.; Fulham, William R.; Todd, Juanita; Budd, Timothy W.; Schall, Ulrich; Hunter, Michael; Hodgson, Deborah M. (Frontiers in Psychology, 2011)
The capacity of the human brain to detect deviance in the acoustic environment pre-attentively is reflected in a brain event-related potential (ERP), mismatch negativity (MMN). MMN is observed in response to the presentation of rare oddball sounds that deviate from an otherwise regular pattern of frequent background standard sounds. While the primate and cat auditory cortex (AC) exhibit MMN-like activity, it is unclear whether the rodent AC produces a deviant response that reflects deviance detection in a background of regularities evident in recent auditory stimulus history or differential adaptation of neuronal responses due to rarity of the deviant sound. We examined whether MMN-like activity occurs in epidural AC potentials in awake and anaesthetised rats to high and low frequency and long and short duration deviant sounds. ERPs to deviants were compared with ERPs to common standards and also with ERPs to deviants when interspersed with many different standards to control for background regularity effects. High frequency and long duration deviant ERPs in the awake rat showed evidence of deviance detection, consisting of negative displacements of the deviant ERP relative to ERPs to both common standards and deviants with many standards. The high frequency deviant MMN-like response was also sensitive to the extent of regularity in recent acoustic stimulation. Anaesthesia in contrast resulted in positive displacements of deviant ERPs. Our results suggest that epidural MMN-like potentials to high frequency sounds in awake rats encode deviance in an analogous manner to the human MMN, laying the foundation for animal models of disorders characterised by disrupted MMN generation, such as schizophrenia.